St. John Chrysostom's Parentage and Education - Jones, A. H. M. (Harvard theological review, 1953)
St. John Chrysostom came, according to Socrates (Hist. Eccl. VI, 3), of a good class Antiochene family (ἐξ ɛὐπατρίδων τῶν ἐκɛῖ). Palladius (Dialogus, 5) gives more specific information — υἱὸς γɛγονὼς τῶν διαπρɛψάντων ɛὐγɛνῶς παρὰ τῇ τάξɛι τοῦ στρατηλάτου τῆς Συρίας. In all commentaries and encyclopedias which I have been able to consult this is taken to mean that his father (Secundus, according to Socrates) had been magister militum per Orientem. The words, however, do mean that Secundus (and his forebears) had served with distinction in the officium of the magister militum per Orientem. The words, however, do mean that Secundus (and his forebears) had served with distinction in the officium of the magister militum per Orientem. Secundus, that is to say, was not a senator of the highest rank, later to be called illustris, but a high grade civil servant. This accords with what John says himself in the de Sacerdotio (I.2) of his fortune and birth, that he was not excessively rich or noble by comparison with his friend Basil. It also accords with the story which his mother tells in the same work (I.5) of the struggle which she had to give him a liberal education; her husband's estate was evidently moderate, since to avoid encroaching on its capital, she was obliged to spend her own dowry.